T cell activation is reduced by the catalytically inactive form of protein tyrosine phosphatase SHP-2 - Dong, Baoxia (Int J Clin Exp Med, 2015)
Src-homology 2 domain-containing tyrosine phosphatase-2 (SHP-2) is a ubiquitously expressed cytosolic tyrosine phosphatase implicated in many different signaling pathways involving cytokine receptors and T and B cell receptors; however, the precise functional role of SHP-2 in T cell signaling is not entirely clear. In this study, we overexpressed a catalytically inactive form of SHP-2 with a classic cysteine 459-to-serine mutation (dnSHP-2) to elucidate the in vivo effects of SHP-2 on T cells. We found that mice overexpressing dnSHP-2 showed reduced T cell activation, presumably due to increased tyrosine phosphorylation of Grb2-binding protein (Gab2) and inhibition of mitogen-activated protein kinase (MAPK) activity. SHP-2 appears to be a positive regulator of the MAPK pathway in T cells, likely through coupling of the multimeric complex to the Ras/MAPK pathway. However, SHP-2 does not appear to affect T cell antigen receptor (TCR)-evoked calcium mobilization, stress-activated protein kinase/c-jun N-terminal kinases (SAPK/JNKs) activation, or overall tyrosine phosphorylation.